Inflection points : how to work and live with purpose - Spielman, Matt (Wiley, 2022)
"What's Your Game Plan? Professional success often conceals a gnawing conflict at one's core--a vague but undeniable sense of lack, that something is askew, off-kilter, or out of place. Even as you pile up accomplishments and accolades, and ascend through the hierarchy of your field, a lingering question resonates in your mind like a ticking clock, or like the steady drip-drip-drip of a faucet as you lay awake in the still of the night: is this really the life I am meant to be living? Is this the life I want? And if it's not, how do I get it? Henry David Thoreau wrote in 1854 that "the mass of men lead lives of quiet desperation (Walden),1" locked in a cycle of daily toil interrupted only by brief bouts of leisure that offer a momentary reprieve, but fail to address the frustrating feeling of existential befuddlement. The world has changed since Thoreau's era, but the observation remains as incisive as ever, and it applies to people from all walks of life, from trades to top tier executive positions. They know there's more they want to get out of life, whether it's more personal satisfaction, a more meaningful contribution to the world, more community connection, more financial security, more intellectual stimulation, or simply more free time to spend alone or with family. But each time they ponder how to find what it is they want--or to know with certainty what they want in the first place--self-doubt blocks action. Is it really possible to have a life and career that is engaging, gratifying, and satisfying?"--